Tree species effects on nutrient cycling and soil biota: A feedback mechanism favouring species coexistence - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Forest Ecology and Management, 2013)
We synthesise a series of independent but integrated studies on the functioning of a mixed Mediterra- nean oak forest to demonstrate the tree–soil interactions underpinning a positive feedback process that sustains the coexistence of two oak species. The studies focused on the foliar functional traits, plant regeneration patterns, biogeochemical cycles, soil microbial biomass and ectomycorrhizal (ECM) fungal diversity associated with the co-dominant evergreen Quercus suber and deciduous Quercus canariensis in a Mediterranean forest in southern Spain. Foliar attributes differed between oak species, with Q. canariensis having higher nutrient content and lower carbon to nutrient ratios and leaf mass per area than Q. suber. These attributes reflected their distinct resource use strategies and adaptation to high and low resource-availability environ- ments, respectively. Leaf-fall nutrient concentrations were higher in Q. canariensis than in Q. suber and were correlated with concentrations in the fresh leaves. Leaf-fall nutrient concentrations influ- enced nutrient return, leaf-fall decay rate and the proportion of nutrients released from decomposing leaf-fall, all of which were higher for Q. canariensis than for Q. suber. This generated a differential net nutrient input into the soil that led to increased soil nutrient concentrations under the canopy of Q. canariensis as compared to Q. suber. The fraction of slowly decomposing leaf-fall that builds up soil organic matter was higher for Q. canariensis, further raising the nutrient and moisture retention of its soils. Differences between species in soil properties disappeared with increasing soil depth, which was consistent with the hypothesised leaf-fall-mediated effect. Tree-species-generated changes in soil properties had further impacts on soil organisms. Soil microbial biomass (Cmic) and nutrients (Nmic, Pmic) were higher under Q. canariensis than under Q. suber and were positively related to soil mois- ture content and substrate availability (particularly soil N). The composition of the ECM fungal com- munity shifted between the two oaks in response to changes in the soil properties, particularly soil Ca and pH. Lower ECM phylogenetic diversity and higher abundance of mycorrhizal species with sapro- phytic abilities were related to the greater soil fertility under Q. canariensis. Overall, the two oak spe- cies generated soil conditions that aligned with their resource-use strategies and would enhance their own competitive capabilities, potentially creating a positive feedback. The two Quercus created soil spatial heterogeneity that could enable their coexistence through spatial niche partitioning. This study demonstrates the critical role of aboveground-belowground interactions underpinning forest commu- nity composition. 
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Feedback processes; Microbial biomass; Mycorrhizal fungi; nutrient cycling; Plant–soil interactions; Quercus

Are Oaks Locally Adapted to Serpentine Soils? - Branco, Sara (Northeastern Naturalist, 2009)
Serpentine soils are extreme habitats known to be involved in processes of local adaptation and speciation of plants. Here I use a greenhouse reciprocal-transplant experiment to compile baseline data for describing patterns of serpentine local adaptation in Quercus ilex subsp. ballota (Holm Oak). I also tested the role of mycorrhizal fungi on the establishment and growth of seedlings on serpentine and non-serpentine soil. Non-serpentine seedlings grew more than serpentine seedlings in all treatments. Plants grew more on non-serpentine soil and mycorrhizal fungi positively influenced seedling growth. I did not find evidence of better seedling performance in their home environment, suggesting the absence of local adaptation. However, I document significant growth differences between serpentine and non-serpentine seedlings, which suggest physiological differences between seedlings from these two soil origins.
doi: 10.1656/045.016.0524doi: 10.1656/045.016.0524The following values have no corresponding Zotero field: publisher: Eagle Hill Institute
Keywords: Mycorrhizal fungi; seedling growth (PG); serpentine

Effect of Sphaerosporella brunnea mycorrhizas on mycorrhization of Quercus ilex × Tuber melanosporum - Garcia-Montero, L. G.; Massimo, G. Di; Manjon, J. L.; García‐Cañete, J. (New Zealand Journal of Crop and Horticultural Science, 2008)
Abstract It is generally accepted that Sphaerosporella brunnea is a significant ectomycorrhizal contaminant in nurseries producing plants mycorrhized with various species of Tuber, and subsequently in truffières after outplanting. At the University of Alcalá, Spain, 397 small plants of Quercus ilex which were mycorrhized with Tuber melanosporum were inadvertently contaminated with S. brunnea, and this contamination was then monitored for 2 years. Sixty percent of the plants were contaminated and had S. brunnea ascomata on the surface of the container on one or several occasions. However, a Spearman test provided no evidence that S. brunnea mycorrhizas affected T. melanosporum mycorrhization whereas other contaminating ectomycorrhizal fungi significantly did. Therefore, it appears that S. brunnea is not detrimental to plants which are well mycorrhized with T. melanosporum.
doi: 10.1080/01140670809510231doi: 10.1080/01140670809510231The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Black truffle; Mediterranean mushroom; Mycorrhizal fungi; mycorrhized contamination; Tuber melanosporum

Problems of using rockroses in Tuber melanosporum culture: soil and truffle harvest associated with Cistus laurifolius - Garcia-Montero, L. G.; Pascual, C.; García-Abril, A.; García-Cañete, J. (Agroforestry Systems, 2007)
The Pe´rigord black trufﬂe (Tuber melanosporum Vittad.) can mycorrhize with rockroses (Cistus L.) in Mediterranean forests. These shrubs may be of interest for trufﬂe cultivation as they produce early carpophores, collaborate in tree mycorrhization and in the survival of Tuber melanosporummycelium. However, there are very few quantitative studies on trufﬂe production associated with Cistus. For this reason, we have carried out a study on the natural production of Tuber melanosporum associated with Cistus laurifolius L. in central Spain. An Anova test conﬁrmed the existence of signiﬁcant differences in carpophore production in four habitats, with and without the presence of C. laurifolius. Twenty-one burns associated with C. laurifolius showed less signiﬁcant production than the rest. We also conﬁrmed that in 122 burns, Tuber melanosporum was always unequivocally associated with the root base of Quercus L. or Corylus L. trees. Similarly, ﬁve trufﬂe-collectors conﬁrmed that they had never found a single burn with carpophore production associated exclusively with rockroses. It has also been statistically veriﬁed that many Cistus die in Tuber melanosporum burns, whereas in old burns with minimum carpophore production, a new colonization of young Cistus has been observed. This study also conﬁrms that C. laurifolius mycorrhizes easily with Tuber melanosporum. We propose that Cistus laurifolius may act as transmitters of Tuber melanosporum, although they do not induce fruiting. Consequently, the commercial cultivation of Cistus laurifolius mycorrhized with Tuber melanosporum for production is not recommended in trufﬂe culture. The results reported substantiate the negative observations in cultivations ofT. melanosporum with other Cistusspecies.
Keywords: host plants; Mediterranean forests; Mushroom production; Mycorrhizal fungi; Woodland products